Permissive State of EMT: The Role of Immune Cell Compartment - Fedele, Vita; Melisi, Davide (Frontiers in Oncology, 2020)
EMT type 3 is a reversible dynamic process recognised as a major determinant of the metastatic event, although many questions regarding its role throughout this process remain unanswered. The ability of cancer cells to migrate and colonise distant organs is a key aspect of tumour progression and evolution, requiring constant tumour cells and tumour microenvironment (TME) changes, as well as constant changes affecting the cross-talk between the two aforementioned compartments.Alterations affecting tumour cells, such as transcription factors, trans-membrane receptors, chromatin remodelling complexes and metabolic pathways, leading to the loss of epithelial phenotype and concomitant acquisition of the undifferentiated mesenchymal phenotype are undoubtedly major players of the EMT process. However, several lines of evidence point out towards a more critical role of TME composition in creating an ‘EMT-permissive state’.The ‘EMT-permissive state’ consists in changes affecting physical and biochemical properties (i.e. stiffness and/or hypoxia) as well as changes of the TME cellular component (i.e. immune-cell, blood vessel, lymphatic vessels, fibroblasts and fat cells) that favour and induce the epithelial mesenchymal transition. In this mini review, we will discuss the role of the tumour microenvironment cellular component that are involved in supporting the EMT, with particular emphasis on the immune-inflammatory cells component.